(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Zahiriddin Muhammad Babur's memoir “Baburname” is well known and well thought-out as a rare source by the world scholars which provide gorgeous information about the history of Central Asian people. His work written in an autobiographical way that contains a vast data about the way of life of people in Central Asia, as abroad scholars called Transoxiana political and social activities of that time, the way of national and cultural life and wonderful customs and traditions. At the same time the literary translation of “Baburname” is also serving as a model of both diachronic and synchronic study from a linguistic translation point of view. The paremiological and phraseological units used in work “Baburname” also served to describe the character of historical figures. This article is devoted to the study of comparative – conceptual analysis of Russian-English translations and suggest the possibility of creating a textual dictionary based on its’ translations and the development of principles of creating dictionary as the work that undergone the history of translation. The English translations made by J. Leyden-W. Erskine (1826), A.S. Beveridge (1921) and W. Thackston (1996) are compared in this article. The tables of phraseological expressions worked out in “Baburname”’s translations, aimed at revealing the cognitive interpretation of the author's point of view.